2021
DOI: 10.1038/s41598-021-95361-4
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of cigarette butts for synthesis of levulinic acid as top value-added chemicals

Abstract: Unprecedented in the literature, levulinic acid (LA), one of the top value-added intermediates of chemical industry, is obtained from cigarette butts as cellulose feedstock by means of a one-pot hydrothermal process carried out at 200 °C for 2 h and catalysed by phosphoric acid. The protocol avoids the use of more aggressive and toxic H2SO4 and HCl, that are generally employed on several cellulose sources (e.g. sludge paper), thus minimizing corrosion phenomena of plants. Neither chemical pre-treatment of butt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The yield 0. 620 g (62% w/w of soy husks) was obtained with a calibration curve and levulinic acid was identified by comparison of the MS spectrum with that reported in the literature [18]. GC/MS (70 eV) m/z (relative intensity): 116 (M+, 3.06), 56 (29.58), 43 (100) (see Supplementary Materials for NMR characterization).…”
Section: Levulinic Acid Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…The yield 0. 620 g (62% w/w of soy husks) was obtained with a calibration curve and levulinic acid was identified by comparison of the MS spectrum with that reported in the literature [18]. GC/MS (70 eV) m/z (relative intensity): 116 (M+, 3.06), 56 (29.58), 43 (100) (see Supplementary Materials for NMR characterization).…”
Section: Levulinic Acid Synthesismentioning
confidence: 99%
“…In the first step, in line with Circular Economy principles, a waste ligno-cellulosic biomass such as soy husks was used as a source of monosaccharides for preparing the first synthetic intermediate, which is levulinic acid. To improve the eco-sustainability of this reaction, thermal hydrolysis was conducted with Amberlyst 15 [17], a solid cation exchange resin bearing sulfonic groups that can act as a heterogeneous acid catalyst in place of the toxic and aggressive strong mineral acids H 2 SO 4 , HCl [18]. Besides limiting the corrosion of the plants, the use of the Amberlyst 15 would allow the easy recycling of the acid catalyst.…”
Section: Improving Eco-sustainability In the Synthesis Of Biobased Su...mentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers have found that biochar can be used as an alternative adsorbent to remove different types of pollutants, such as heavy metals, nutrients, and pharmaceuticals, from aqueous solutions [ 20 ]. Many raw materials and their resulting biochars have low specific surface or low catalytic activity, so these materials are pre-treated (activated) with acids, such as sulphuric acid [ 21 ] or phosphoric acid [ 22 ]. To the best of our knowledge, biochars from olives stones have not been applied as biocatalyst so far.…”
Section: Introductionmentioning
confidence: 99%